Propane dehydrogenation over alumina-supported palladium and palladium-tin catalysts - Valecillos, José; Rodríguez, Douglas; Méndez, Jonathan; Solano, Roger; González, Carlos; Acosta, Thaís; Sánchez, Jorge; Arteaga, Geomar (Ciencia)
The dehydrogenation of propane over Pd/Al2O3 and Pd-Sn/Al2O3, catalysts was studied as a function of Sn content, addition of chlorine, and reaction time. Bimetallic catalysts were prepared by incipient wetness impregnation of a Cl-free Pd/ï§-Al2O3, catalyst with solutions of SnC4H4O6,(tin tartrate) and SnCl2 + HCl. Atomic Sn/Pd ratios were 0.07 and 0.22 for the Cl-containing catalysts, and 0.04 for the Cl-free catalyst. The catalysts were calcined at 400°C and reduced in H2 at 500°C. These materials were characterized by temperature programmed reduction (TPR) and H2 and CO chemisorption. The reaction was carried out at 500°C and a molar H2/C3H8 ratio of 16. The addition of Sn strongly modified the CO adsorption on Pd, particularly when Cl was present. In contrast, H2 adsorption was not affected by Sn addition. TPR profile of Pd/Al2O3 showed two peaks at 5 and 18°C, attributed to the reduction of large and small PdO particles, respectively. The formation of ï¢-palladium hydride phases was evidenced by two negative peaks of H, desorption at 61 and 85°C. The addition of Sn caused (i) the diminution in size of the large PdO particles, resulting a symmetrical peak at 15°C. (ii) a small peak at 53ºC, ascribed to the reduction of a small fraction of SnO2 assisted by Pdº, and (iii)t he formation of a ï¢-PdH phase, which produced a negative peak at 72°C. Initial activity of Pd/Al2O3 was high, but it deactivated due to coking. Coke had a strong negative effect on hydrogenolysis reactions, increasing the dehydrogenation selectivity. With the addition of Sn. the initial activity of Pd decreased, the dehydrogenation selectivity increased and the catalytic stability improved. Tin and coke had similar effects on catalytic properties of Pd/Al2O3. The results were rationalized in terrns of the site-blocking effect of Sn and of its repulsive. interactions.